Regime gerencial e integridade em organizaç\~oes - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The kind of managerial regime shapes motivation as well as internal institutions and people's lives within the organizations. As a consequence, it makes organizational wrongdoings more likely or unlikely to occur. On the one hand, in the regime of command and control, the structure of the organization, particularly hierarchy and internal discipline, is tailored to preserve and strengthen the power, the status and the prestige of persons occupying the top posts. Intraorganizational communication is mainly one-way, from above. Management gets on by distributing prizes and penalties. On the other hand, an organization has a community in its core. After having adopted a multilateral collaborative regime, the organization becomes aware of its social function and takes care of its people. Hence, the main quality in focus is the quality of how people are treated. A central activity of management is bringing about quality of life in work, two-way communication and flat hierarchy. Intrinsic motivation prevails upon economic incentives.
Keywords: D73; A13; B40; 330; managerial regime; human relations; organizational wrongdoings; ethics in organizations